Laser active thermography for debonding detection in FRP retrofitted concrete structures. (September 2020) - Xu, Ying; Hwang, Soonkyu; Wang, Qingyuan; Kim, Donggun; Luo, Congcong; Yang, Jinyeol; Sohn, Hoon
Abstract: The surface of Fiber Reinforced Polymer (FRP) concrete is heated with a line laser beam, and the corresponding heat responses are measured by an infrared (IR) camera. Local heat distribution anomalies caused by interfacial debonding between FRP and concrete are automatically traced and detected as defect based on image processing of IR images. Through numerical simulations and lab-scale experiments, the performance of the laser active thermography for the FRP retrofitted concrete inspection was compared with the performance of a halogen lamp based thermography. This comparison shows that the laser active thermography offers a longer inspection range (over 5 m), better damage sensitivity (detecting damage larger than 10 mm diameter), lower power consumption (15W laser excitation), and reduced false alarms due to external noises.